Examining How Entrepreneurial Motivation, Family Environment, and Entrepreneurship Education Affect Students' Desire to Become Entrepreneurs, with Instrumental Readiness Serving as a Moderating Factor - Krisnanti; Inggarwati, Komala (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The study's goal is to find out how entrepreneurial motivation, family environment, and entrepreneurship education affect the desire to be an entrepreneur among UKSW dormitory students, with instrumental readiness acting as a moderating variable. This study uses the association research method with a quantitative approach and has 152 respondents. All of them are students living in UKSW dorms and are the result of our own data processing. A formula called the Solvin formula was used to find the minimum number of respondents. This study used a non-probability sampling method, especially purposeful sampling and accidental sampling. The study shows that entrepreneurial motivation, family environment, and entrepreneurship education all have a positive effect on the entrepreneurial interest of UKSW dorm residents. The moderating variable instrumental readiness can make the effects of entrepreneurial drive, family environment, and entrepreneurship education stronger on the desire to be an entrepreneur among UKSW dormitory students.